Focus particles in German : syntax, prosody, and information structure - Sudhoff, Stefan, 1977- (Linguistik aktuell ;, 2010)
This study explores the grammar of focus particles in German. It gives a thorough description and analysis of focus particle constructions and links their syntactic, semantic, and information structural properties to their prosodic characteristics. The study also shows that focus particles present a particularly well-suited subject for the investigation of the modularity of grammar in general. The first part of the book deals with the syntax, semantics, and pragmatics of focus particle constructions and results in a modular account of the relation between their word order, information structur.